Penyelesaian Sistem Persamaan Linear Fuzzy Menggunakan Metode Dekomposisi Crout - Aulia Rindu Permata; Arnellis Arnellis (Journal of Mathematics UNP, 2018)
Abstract  Variables and constants from the system of linear equations commonly studied are real numbers because the problems that are resolved are clear. In fact, not all problems are clear, but still in a vague state, so to overcome them, a fuzzy linear equation system is needed. Fuzzy linear equation systems have variables and constants in the form of fuzzy numbers while the coefficients are real numbers. This study uses Crout's decomposition method in solving fuzzy linear equation systems. Crout Decomposition Method is a method that factifies the coefficient coefficient A of the system equation Ax = y to be a matrix multiplication LU where L is a matrix of the lower triangle and U is a triangular matrix on which the main diagonal is one. The results of this study found that Crout's decomposition method can be used in solving fuzzy linear equation systems.